A Study of The Treatment of Larvae Vannamei Shrimp (Litopenaeus vannamei) In Banyuwangi - Ramli, Taufik Hadi; Suhermanto, Achmad; Andi, Rudi; Sangkia, Frederik Dony (Jurnal Ilmiah Platax, 2023)
Vannamei shrimp (Litopenaeus vannamei) is a brackish water commodity that is currently in great demand and is a leading producer of the aquaculture sector in Indonesia. This is because some of the advantages possessed by the vannamei shrimp, among others, can be maintained with a high stocking density, rapid growth, has a high resistance to disease and environmental changes. The mating process occurs through four stages, namely approach, pursuit, pride, and mating. This process can be known by looking at the behavior of the male parent who swims to follow the female parent. They both looked like a chase. Then the male parent swims parallel to the female and turns her body towards the female shrimp's belly. After that, the male grabs the female and releases sperm that attach to the thellycum. In the maintenance of larvae that must be considered is the management of water quality and feed management. This is because water is a living medium for aquatic organisms, so it determines the survival of larvae. During the period of high maintenance and market, demand continues to increase where the shrimp farming process includes the hatchery stage to enlargement. Vannamei shrimp hatchery activities are inseparable from the availability of quality fry